Preparation and Physicochemical Properties of [6]Helicenes Fluorinated at Terminal Rings - Církva, Vladimír; Jakubík, Pavel; Strašák, Tomáš; Hrbáč, Jan; Sýkora, Jan; Císařová, Ivana; Vacek, Jan; Žádný, Jaroslav; Storch, Jan (The Journal of organic chemistry, 2019)
The first racemization-stable helicene derivatives fluorinated at terminal rings, 1,2,3,4-tetrafluoro[6]helicene (6) and 1,2,3,4,13,14,15,16-octafluoro[6]helicene (15), were synthesized via the Wittig reaction followed by oxidative photocyclization in an overall yield of 41% of 6 and 76% of 15. The changed electronic structure in fluorinated helicenes was reflected in a slight shift of UV-vis absorption, fluorescence excitation, and emission spectra maxima when compared to unsubstituted [6]helicene. Cyclic voltammetry revealed a moderate decrease in the HOMO-LUMO gap with increasing fluorination. The specific rotation of tetrafluoro[6]helicene 6 enantiomers was found to be approximately 25% lower than that of unsubstituted [6]helicene. The theoretical study of the racemization barrier suggested a reasonable shift toward higher energy with increasing fluorination. The increasing fluorination also significantly affected the intermolecular interactions in the crystal lattice. The observed CH···F interactions led to the formation of 1D-molecular chains in the crystal structures of both fluorinated helicenes.